Bioabsorbable particles and methods of use thereof

By developing bioabsorbable particles containing polymer matrix, antisense oligonucleotides and cationic lipids, the problem of difficult delivery of nucleic acid active agents to the colon is solved, and efficient therapeutic effects and safety are achieved.

CN119584957APending Publication Date: 2025-03-07WL GORE & ASSOC INC
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202280088820.3
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Priority Date
2022-03-02
Filing Date
2022-12-20
Publication Date
2025-03-07

AI Technical Summary

Technical Problem

In the medical field, nucleic acid active agents used in particular for the treatment of inflammatory bowel disease are difficult to effectively deliver to the colon, resulting in poor treatment results.

Method used

Develop a bioabsorbable particle preparation including polymer matrix, antisense oligonucleotide (ASO) and cationic lipids, prepare nano or microparticles through sonication technology, ensure that the average particle size of the particles is less than 300 nm, and release nucleic acids through biodegradation in the patient's body.

Benefits of technology

This method can effectively deliver nucleic acid active agent to the colon, improve the effect of treating inflammatory bowel disease, and reduce drug residues through biodegradation and improve safety.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119584957A_ABST
    Figure CN119584957A_ABST
Patent Text Reader

Abstract

The present disclosure provides bioabsorbable particles with nucleic acids. The bioresorbable particle further includes a bioresorbable polymer matrix and a lipid salt, both of which can be altered to affect particle properties. The bioresorbable particles may be administered to a patient to treat a disease. Methods of making and using the bioabsorbable particles thereof are also provided.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present disclosure generally relates to bioabsorbable particles. More specifically, the disclosure relates to particles comprising a polymer, a lipid salt, and a nucleic acid agent for use in medical treatment. Background Art

[0002] Numerous developments in the medical field have led to new technologies to combat disease. One such development is the use of active agents involving nucleic acids to treat inflammatory diseases, such as inflammatory bowel disease (IBD). However, delivering active agents to the colon to treat IBD can be difficult due to physiological challenges, biochemical barriers, and environmental barriers, including those associated with mucus and epithelium. Summary of the invention

[0003] In one aspect (Aspect 1), a formulation comprises a plurality of bioresorbable particles, each bioresorbable particle comprising a polymer matrix, an antisense oligonucleotide (ASO) encapsulated within the polymer matrix, and a cationic lipid encapsulated within the polymer matrix, wherein the plurality of bioresorbable particles contain at least about 1 weight % of the antisense oligonucleotide (ASO).

[0004] In another aspect (Aspect 2), according to Aspect 1, the average particle size of the plurality of bioresorbable particles is less than 300 nm.

[0005] In another aspect (Aspect 3), according to any of Aspects 1-2, the plurality of bioresorbable particles comprises at least about 5 wt % ASO.

[0006] In another aspect (Aspect 4), according to any one of Aspects 1-3, the plurality of bioresorbable particles comprises at least about 10 wt % ASO.

[0007] In another aspect (Aspect 5), according to any one of Aspects 1-4, the plurality of bioresorbable particles comprises at least about 15 wt % ASO.

[0008] In another aspect (Aspect 6), according to any one of Aspects 1-5, the polymer matrix comprises trimethylene carbonate (TMC). In another aspect (Aspect 7), according to any one of Aspects 1-6, the polymer matrix comprises a copolymer of TMC and polylactic acid (PLA).

[0009] In another aspect (Aspect 8), according to Aspect 7, the ratio of TMC to PLA is about 25:75.

[0010] In another aspect (Aspect 9), according to any one of Aspects 1-8, the polymer matrix comprises poly(lactic-co-glycolic acid) (PLGA) copolymer.

[0011] In another aspect (Aspect 10), according to any one of Aspects 1-9, the formulation comprises a surface polymer attached to the surface of each bioresorbable particle.

[0012] In another aspect (Aspect 11), according to Aspect 10, the surface polymer comprises polyethylene glycol (PEG).

[0013] In another aspect (Aspect 12), according to Aspect 11, the bioresorbable particles comprise at least 5 wt% PEG.

[0014] In another aspect (Aspect 13), according to any one of Aspects 1-12, the plurality of bioresorbable particles comprises at least about 10 wt % to about 40 wt % of the cationic lipid.

[0015] In another aspect (Aspect 14), according to any one of Aspects 1-13, the plurality of bioresorbable particles comprises at least about 20 wt% to about 30 wt% cationic lipid.

[0016] In another aspect (Aspect 15), according to any one of Aspects 1-14, the plurality of bioresorbable particles comprises nanoparticles.

[0017] In another aspect (Aspect 16), according to any one of Aspects 1-14, the plurality of bioresorbable particles comprises microparticles.

[0018] In another aspect (Aspect 17), a method of treating a patient in need thereof comprises the steps of providing the patient with a formulation according to any one of Methods 1-16 and allowing sufficient time for the polymer matrix to degrade in the patient and release the nucleic acid in the patient.

[0019] In one aspect (Aspect 18), a method for preparing a bioabsorbable particle formulation comprises dissolving a structural polymer and a cationic lipid in a solvent, adding a nucleic acid having a length of 2 to 75 nucleotides to the dissolved structural polymer and cationic lipid, sonicating the mixture of the structural polymer, the cationic lipid and the nucleic acid in a first sonication treatment to produce a water-in-oil emulsion, adding an aqueous solution to the water-in-oil emulsion, sonicating the water-in-oil emulsion in a second sonication treatment to produce a water-in-oil-in-water emulsion, adding water to the water-in-oil-in-water emulsion, collecting a plurality of particles from the water-in-oil-in-water emulsion, and washing the plurality of particles.

[0020] In another aspect (Aspect 19), according to Aspect 18, the cationic lipid and the structural polymer are dissolved in a ratio of about 1:4 mass ratio to about 1:1 mass ratio.

[0021] In another aspect (Aspect 20), according to Aspect 18 or 19, the nucleic acid is an antisense oligonucleotide (ASO) loaded into the plurality of particles in an amount of about 5 wt% to about 20 wt%.

[0022] In another aspect (Aspect 21), according to any one of Aspects 18-20, the first ultrasonic treatment and the second ultrasonic treatment are performed in an ice bath.

[0023] In another aspect (Aspect 22), according to any one of Aspects 18-21, the aqueous solution is a polyvinyl alcohol solution.

[0024] In another aspect (Aspect 23), according to any one of Aspects 18-22, the step of collecting a plurality of particles from the emulsion is performed by centrifugation.

[0025] In another aspect (Aspect 24), according to any one of Aspects 18-23, the method comprises lyophilizing the oil solution in the presence of a sugar and a buffer.

[0026] In another aspect (Aspect 25), according to Aspect 24, the sugar is trehalose.

[0027] In another aspect (Aspect 26), according to Aspect 24 or 25, the buffer is histidine.

[0028] In one aspect (Aspect 27), a method of treating a patient in need thereof comprises (1) delivering a plurality of particles to the patient, wherein each particle comprises a polymer matrix, a nucleic acid having a length of 2 to 75 nucleotides encapsulated in the polymer matrix, and a cationic lipid encapsulated in the polymer matrix, wherein the ratio of the cationic lipid to the polymer matrix in each particle is from about 1:4 by weight to about 1:1 by weight, and (2) allowing sufficient time for the polymer matrix to biodegrade in the patient and release the nucleic acid.

[0029] In another aspect (Aspect 28), according to Aspect 27, the nucleic acid is an antisense oligonucleotide (ASO) loaded in multiple particles at about 5 wt% to about 20 wt%, and the cationic lipid is one of 1,2-bis-O-octadecenyl-3-trimethylammonium propane chloride (DOTMA) or 1,2-dioleoyl-3-trimethylammonium propane chloride (DOTAP).

[0030] In another aspect (Aspect 29), according to Aspect 27 or 28, the polymer matrix biodegrades in the colon of the patient.

[0031] In another aspect (Aspect 30), according to any one of Aspects 27-29, each particle further comprises a surface polymer on the surface of each particle, the surface polymer comprising polyethylene glycol (PEG).

[0032] In another aspect (Aspect 31), according to Aspect 30, each particle comprises at least 5 wt% PEG.

[0033] In another aspect (Aspect 32), according to any of Aspects 27-31, the plurality of particles comprises nanoparticles.

[0034] In another aspect (Aspect 33), according to any one of Aspects 27-32, the patient suffers from at least one of inflammatory bowel disease, cardiovascular disease, hypertension, chronic heart failure, diabetes, Parkinson's disease, prostate cancer and chronic kidney disease.

[0035] In one aspect (Aspect 34), a formulation comprises a plurality of bioresorbable particles, each bioresorbable particle comprising a polymer matrix, a nucleic acid encapsulated in the polymer matrix, a cationic lipid encapsulated in the polymer matrix, and a surface polymer attached to the surface of each bioresorbable particle, wherein the surface polymer comprises polyethylene glycol (PEG) and each bioresorbable particle comprises at least 5 weight percent PEG. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] The accompanying drawings are used to help further understanding of the present disclosure, and are incorporated in and constitute a part of the specification. The accompanying drawings illustrate embodiments of the present disclosure and together with the description serve to explain the principles of the present disclosure.

[0037] Figure 1 is a schematic diagram of a bioresorbable nanoparticle according to at least one embodiment.

[0038] Figure 2 is a schematic diagram of a bioresorbable nanoparticle including a surface polymer according to at least one embodiment.

[0039] Figure 3 is prepared according to at least one embodiment Figure 1 Flow chart of the method for producing bioresorbable nanoparticles.

[0040] Figure 4 is with Figure 3 Similar preparation according to at least one embodiment Figure 2 Partial flow chart of a method for producing bioresorbable nanoparticles.

[0041] Figure 5 According to at least one embodiment, Figure 1-2 Flowchart of a method of treating a patient with bioresorbable nanoparticles.

[0042] Figure 6 is a graph showing the relationship between lipid loading level and nanoparticle diameter according to at least one embodiment.

[0043] Figure 7 is a graph showing the relationship between lipid levels and nucleotide loading according to at least one embodiment.

[0044] Figure 8 is a graph showing the relationship between lipid levels and zeta potential according to at least one embodiment.

[0045] Fig. 9 and Fig.10 A graph showing the relationship between incubation and nucleotide release for a plurality of experiments performed according to at least one embodiment.

[0046] Fig.11 Particle distributions of TFF-cleaned nanoparticles, reconstituted particles in deionized water and phosphate buffered saline (PBS) are shown in accordance with at least one embodiment.

[0047] Fig.12 is the gel assay discussed in the Examples according to at least one embodiment.

[0048] Fig.13 is a scanning electron micrograph (SEM) image of bioresorbable nanoparticles formed according to at least one embodiment. DETAILED DESCRIPTION

[0049] Definitions and terminology

[0050] This disclosure should not be interpreted in a limiting manner. For example, the terms used in this application should be interpreted broadly according to the meaning that people in the field would give to such terms.

[0051] The term "about" or "approximately" means within an acceptable error range that can be determined by one of ordinary skill in the art for a particular value, which will depend in part on how the value is measured or determined, for example, the limits of the measurement system. For example, according to the practice in the art, "about" can refer to 1 or more than 1 standard deviation. Alternatively, "about" can refer to a range of up to 20%, up to 10%, up to 5%, or up to 1% of a given value. Alternatively, the term can mean within an order of magnitude, such as within 5 times or 2 times a value. Where specific values ​​are described in the application and claims, unless otherwise indicated, the term "about" should be assumed to mean that the specific value is within an acceptable error range.

[0052] Description of various embodiments

[0053] It will be appreciated by those skilled in the art that various aspects of the present disclosure may be implemented by any number of methods and devices configured to implement the desired effects. It should also be noted that the drawings referenced herein are not necessarily drawn to scale, but may be enlarged to illustrate various aspects of the present disclosure, and in this regard, the drawings should not be considered limiting.

[0054] First reference Figure 1 , a schematic diagram of an exemplary bioabsorbable particle, nanoparticle 100 is shown. Nanoparticle 100 includes surface 110, polymer matrix 120, lipid 140 and nucleic acid 150. Although lipid 140 and nucleic acid 150 are shown as separated from each other in nanoparticle 100, it is understood that lipid 140 is preferably complexed with nucleic acid 150 in nanoparticle 100. In an exemplary embodiment, nanoparticle 100 has a size of about 300nm or less. In another exemplary embodiment, nanoparticle 100 has a size of about 100nm to about 300nm. In a most preferred embodiment, nanoparticle 100 has a size of about 200nm to about 300nm. Although nanoparticle 100 is shown and described herein, the present disclosure also relates to microparticles having a size greater than about 300nm, such as about 500nm, 750nm, 1000nm (1μm) or more. In addition, the nanoparticle 100 can have a neutral or nearly neutral charge, such as a zeta potential of from about -20 mv to about +20 mv. Alternatively, the zeta potential of the nanoparticle 100 can be from about -10 mv to about +10 mv. Preferably, the neutral or nearly neutral nanoparticle 100 can have a zeta potential of about 0 mv.

[0055] It should be noted that Figure 1 It is only a schematic diagram of nanoparticle 100, and lipids 140 and nucleic acids 150 are described as heterogeneous features in polymer matrix 120 for illustrative purposes only. Polymer matrix 120, lipids 140 and nucleic acids 150 can be completely or partially homogeneous. Alternatively, polymer matrix 120, lipids 140 and nucleic acids 150 can be completely or partially heterogeneous. Polymer matrix 120, lipids 140 and nucleic acids 150 can be completely or partially emulsions. Polymer matrix 120, lipids 140 and nucleic acids 150 can be completely or partially suspensions. Polymer matrix 120, lipids 140 and nucleic acids 150 can be completely or partially any other form of mixtures understood and known by those skilled in the art. Alternatively, polymer matrix 120, lipids 140 and nucleic acids 150 can be any material state. For example, nucleic acid 150 can be a solid or liquid encapsulated in polymer matrix 120 (e.g., solid polymer matrix). Each of polymer matrix 120, lipids 140 and nucleic acids 150 is further described below.

[0056] In non-limiting embodiments, the polymer matrix 120 of the nanoparticle 100 is a bioabsorbable or biodegradable polymer. The polymer matrix 120 can be hydrophobic in nature to promote slower degradation than a hydrophilic matrix. The polymer matrix 120 can also exhibit low acid degradation to minimize inflammation. In one embodiment, the polymer matrix 120 can be a polymer based on trimethylene carbonate (TMC), such as a copolymer of TMC and polylactic acid (PLA), hereinafter referred to as "PLA:TMC". PLA:TMC copolymers can be synthesized using methods known in the art, for example, by combining TMC monomers with suitable lactic acid comonomers, such as L-lactic acid comonomers to produce poly(L, lactic acid-TMC), hereinafter referred to as "L-PLA:TMC"; with D-lactic acid comonomers to produce poly(D, lactic acid-TMC), hereinafter referred to as "D-PLA:TMC"; and with comonomers of L-lactic acid, D-lactic acid and TMC to produce poly(DL, lactic acid-TMC), hereinafter referred to as "D,L-PLA:TMC". The weight ratio of D-PLA to TMC of the PLA:TMC copolymer may be 55% to 45% (55:45) or 75% to 25% (75:25), the weight ratio of L-PLA to TMC may be 55% to 45% (55:45) or 75% to 25% (75:25), and the weight ratio of D,L-PLA to TMC may be 50% to 50% (50:50) or 75% to 25% (75:25) (all based on weight). In some aspects, the PLA:TMC copolymer may include 45 to 60 weight % PLA and 40 to 55 weight % TMC. In another embodiment, the polymer matrix 120 may include a terpolymer of PLA, TMC and another polymer (such as polyethylene glycol (PEG)), hereinafter referred to as "PLA:TMC:PEG". In yet another embodiment, the polymer matrix 120 may include a poly(lactic-co-glycolic acid) (PLGA) copolymer containing PLA and polyglycolic acid (PGA) comonomers.

[0057] The type of polymers used, the ratio of polymers used, and the method of preparing the polymer matrix 120 can all be varied to adjust the properties of the polymer matrix 120. These properties can include: the ability of the polymer matrix 120 to degrade or otherwise release the nucleic acid 150, the effect of pH on the polymer matrix 120, the size of the nanoparticle 100, the amount of lipid 140 and nucleic acid 150 loaded into the nanoparticle 100, the physical properties of the nanoparticle 100 (e.g., density, melting point, glass transition temperature, modulus, etc.), and the chemical properties of the nanoparticle 100 (e.g., molecular weight, polarity, charge, etc.). In one embodiment, the polymer matrix 120 is formulated to degrade in the gastrointestinal tract of a patient. Specifically, the polymer matrix 120 can be formulated to degrade in the colon of a patient.

[0058] In one embodiment, the lipid 140 of the nanoparticle 100 is a cationic lipid salt. Specifically, the lipid 140 can be 1,2-dioleoyl-3-trimethylammonium propane chloride (DOTAP) or 1,2-di-O-octadecene-3-trimethylammonium propane chloride (DOTMA). In other embodiments, any lipid 140 can be used. The nanoparticle 100 can be loaded with about 10% to about 40% by weight of lipid 140 or about 20% to about 30% by weight of lipid 140, but the amount of lipid 140 loaded in the nanoparticle 100 can be changed to adjust the characteristics of the nanoparticle 100, such as the size, loading and / or release of nucleic acid 150, charge, zeta potential, etc. The loading of lipid 140 can also be expressed as a ratio relative to the amount of polymer matrix 120. The nanoparticle 100 can be loaded with lipid 140 so that the ratio of lipid 140 to polymer matrix 120 is about 1:4 mass ratio.

[0059] The nanoparticle 100 can be loaded with lipid 140 so that the ratio of lipid 140 to polymer matrix 120 is about 1:1 by mass. The nanoparticle 100 can be loaded with lipid 140 so that the ratio of lipid 140 to polymer matrix 120 is about 1:2 by mass. The nanoparticle 100 can be loaded with lipid 140 so that the ratio of lipid 140 to polymer matrix 120 is about 3:4 by mass. The loading amount of lipid 140 can also be expressed as a ratio relative to the amount of nucleic acid 150. The nanoparticle 100 can be loaded with lipid 140 so that the ratio of lipid 140 to nucleic acid 150 is about 1:1 by mass. The nanoparticle 100 can be loaded with lipid 140 so that the ratio of lipid 140 to nucleic acid 150 is about 2:1 by mass. The nanoparticle 100 can be loaded with lipid 140 so that the ratio of lipid 140 to nucleic acid 150 is about 5:4 by mass. The nanoparticle 100 can be loaded with lipid 140 so that the ratio of lipid 140 to nucleic acid 150 is about 7:4 by mass. The nanoparticle 100 can be loaded with lipid 140 such that the ratio of lipid 140 to nucleic acid 150 is approximately 3:2 by mass. The loading of lipid 140 allows for more subtle tuning of the properties of the nanoparticle 100. In general, an increase in the amount of lipid 140 loaded in the nanoparticle 100 corresponds to an increase in the nucleic acid 150 loading, and an increase in the zeta potential ( Figure 7-8 ). It is generally desirable that the nanoparticle 100 has a neutral or slightly negative charge, which can be changed by the loading amount and type of lipid 140 in the nanoparticle 100.

[0060] The nucleic acid 150 of nanoparticle 100 comprises short chain nucleotides. In some embodiments, nucleic acid 150 is an oligonucleotide. Oligonucleotides are short DNA and / or RNA molecules and / or oligomers, which are widely used in disease treatment, gene detection and research. The use of oligonucleotides as therapeutic agents depends on their ability to interfere with the basic mechanism of protein synthesis in a sequence-specific manner, whether by binding to mRNA transcribed from a gene or directly binding to a target gene. The oligonucleotide is an antisense oligonucleotide (ASO). ASO can be used to regulate gene expression and treat inflammatory and neoplastic diseases.

[0061] Oligonucleotides are characterized by the sequence and number of nucleotide residues that make up the entire molecule. The number of DNA and / or RNA nucleotide units that make up the molecule generally indicates the length of the oligonucleotide. For example, an oligonucleotide of 10 nucleotides or bases is a "10-mer" oligonucleotide. Chemical modifications are often made to the backbone or sugar rings, for example, to increase nuclease resistance or specificity for a target.

[0062] Nucleic acids with less than 75 nucleotides are preferred to avoid shearing of the nucleic acid during the sonication step used to produce the bioresorbable particles. More preferably, the nucleic acid has less than 40 nucleotides.

[0063] The nanoparticle 100 can be loaded with at least 5 wt % nucleic acid 150, about 5 wt %, about 10 wt %, about 15 wt %, about 20 wt %, about 25 wt %, about 30 wt % or more nucleic acid 150, but the amount can be varied to adjust the properties of the nanoparticle 100.

[0064] Nanoparticle 100 is configured to degrade in the gastrointestinal tract of patient and release nucleic acid 150 for medical treatment. In one example, nanoparticle 100 is configured to be absorbed / degraded in the colon of patient, so nucleic acid 150 can be directly delivered in the colon to treat inflammatory bowel disease (such as Crohn's disease, ulcerative colitis, etc.). In addition, nanoparticle 100 can be configured to degrade, be absorbed or release active agent in any organ of patient or along any point of gastrointestinal tract (such as stomach, intestine). Although in the illustrated embodiment, nanoparticle 100 loads the nucleic acid 150 that is suitable for treating inflammatory bowel disease, in other embodiments, nanoparticle 100 can load nucleic acid 150 or any active ingredient or medicine that is suitable for treating various medical problems, and various medical problems include but are not limited to, cardiovascular disease, hypertension, chronic heart failure, diabetes, Parkinson's disease, prostate cancer and chronic kidney disease.

[0065] Next refer to Figure 2 , another exemplary nanoparticle 100 ′ is shown. Figure 2 The nanoparticles 100' and Figure 1Similar elements are identified with similar reference numerals except as described herein. Figure 2 As shown, nanoparticle 100' may also include surface polymer 170'. In one embodiment, surface polymer 170' is covalently bonded to at least surface 110' of nanoparticle 100'. A non-limiting example of surface polymer 170' is a copolymer of PLA and polyethylene glycol (PEG). When PEG is used as surface polymer 170' (used alone or in a copolymer), surface 110' may be described as "PEGylated". Surface polymer 170' may be added to surface 110' of nanoparticle 100' by forming nanoparticle 100' in the presence of a physical blend of surface polymer 170', or surface polymer 170' may be added to surface 100' of nanoparticle 100' by forming a terpolymer with surface polymer 170' and polymer matrix 120'. In addition, surface polymer 170' may be added to surface 110' by a connecting group located on nanoparticle 100'. Non-limiting examples of such linking groups include 1-ethyl-3-(3-dimethylaminopropyl)carbodiimide (EDC), succinimidyl active esters, and NH 2 -PEG. In other embodiments, surface polymer 170' can be added to surface 110' after nanoparticle 100' is prepared. Surface polymer 170' can contribute to the migration of nanoparticle 100', the bioabsorption of nanoparticle 100', the degradation of nanoparticle 100', or change the physical or chemical properties of nanoparticle 100'. Each nanoparticle 100' can include at least about 1 weight %, at least about 5 weight %, at least about 10 weight %, at least about 15 weight % or at least about 20 weight % of surface polymer 170'. In some embodiments, each nanoparticle can include about 1 weight % to about 20 weight %, about 1 weight % to about 15 weight %, about 1 weight % to about 10 weight %, about 5 weight % to about 20 weight %, about 5 weight % to about 15 weight %, or about 5 weight % to about 10 weight %.

[0066] Reference now Figure 3 , showing the preparation Figure 1Method 300 of making nanoparticles 100. Method 300 of making includes dissolving 310 in a structural polymer matrix 120 and a lipid salt 140 in a suitable solvent, adding nucleic acid 150 and sonicating 320 the mixture to produce a water-in-oil emulsion, adding an aqueous solution 330 such as polyvinyl alcohol, sonicating 340 the resulting mixture to produce a water-in-oil-in water-in-oil emulsion, adding water 350, collecting 360 the nanoparticles 100 by drying, centrifugation or other suitable methods, and washing 370 the nanoparticles 100. While this method demonstrates one method of making nanoparticles 100, additional steps can be added to method 300, including, for example, slowly shaking the water-in-oil emulsion for several hours, stirring the double emulsion overnight after adding water 350, dispersing the nanoparticles 100 in water after cleaning 370, and / or freeze-drying the nanoparticles 100 after cleaning 370. The step of dissolving 310 can be completed with any solvent that can effectively dissolve the polymer matrix 120 and the lipid 140, such as but not limited to dichloromethane. The steps of ultrasonic treatment 320, 340 can be performed on an ice bath. In other embodiments, ultrasonic treatment can be performed at different temperatures, different time lengths and different amplitudes. See Example 7 for an embodiment of the method 300 of making. Once the nanoparticles 100 are made, they are analyzed as known in the art and discussed in the examples below.

[0067] Reference now Figure 4 , showing the preparation Figure 2 The method 300' of the nanoparticle 100'. Figure 4 The manufacturing method 300' shown is Figure 3 The method 300 of making is similar, and similar elements are identified with similar reference numerals except as described herein. Figure 4 As shown, during the dissolution 310', the surface polymer 170' is added to the polymer matrix 120' and the lipid salt 140'.

[0068] Reference now Figure 5 , showing a processing method 400. Figure 1 The processing method 400 of the nanoparticle 100 is described, but the processing method 400 is also applicable to Figure 2The method of treatment 400 includes administering 410 the nanoparticles 100 to a patient, wherein the polymer matrix 120 will degrade 420 in the patient's body, followed by the release 430 of the nucleic acid 430 from the nanoparticles 100 into the patient's body. The nanoparticles 100 can be administered orally 410 via a pill, tablet, or solution, or can be administered 410 via injection. If administered orally, the nanoparticles 100 can initially be located in a capsule (not shown) that degrades at a certain point or specific area in the gastrointestinal tract. In one embodiment, the capsule has an enteric coating that allows the capsule to degrade when the pH changes.

[0069] Nanoparticles 100 are configured to be bioabsorbable so that polymer matrix 120, lipids 140 and / or nucleic acids 150 can be absorbed by the human body. One potential absorption method is through intracellular pinocytosis. In pinocytosis, the cell membrane extends and folds around extracellular material to form a bag that produces internalized vesicles. The vesicles eventually fuse with lysosomes, where the contents (in this case, nanoparticles 100) are digested. In this way, the polymer matrix 120 can be degraded within the cells in the gastrointestinal tract by the internal digestion process of the cells, and the nucleic acids 150 will then be delivered to the cells. In this way, nucleic acids 150 can be delivered to the target area of ​​the patient to treat various diseases such as irritable bowel syndrome, cardiovascular disease, hypertension, chronic heart failure, diabetes, Parkinson's disease, prostate cancer or chronic kidney disease.

[0070] Figure 1-2 The nanoparticles 100, 100' and Figure 3-5 The method shown is provided as an example of various features of the device / method, and although the combination of these illustrated features is clearly within the scope of the invention, this example and its schematic diagram do not mean that the inventive concept provided herein is subject to fewer features, additional features or Figure 1-5 For example, in various embodiments, Figure 5 The steps of the method shown may include referring to Figure 3 It should also be understood that the reverse is also true. In addition, Figure 1 One or more of the components described in Figure 2 in addition to or as a replacement for the components described in .

[0071] Test Method

[0072] It should be understood that although certain methods and apparatus are described below, other methods or apparatuses determined to be suitable by one of ordinary skill in the art may alternatively be used.

[0073] Intrinsic viscosity

[0074] Hexafluoroisopropanol (HFIP) was used as the extraction solvent and the intrinsic viscosity (IV) was measured using a Cannon MiniPV-HX automatic viscometer.

[0075] Nanoparticle size

[0076] Nanoparticle size was measured using an Ultrasizer (Marlven Panalytical) in multi-angle light scattering mode.

[0077] Charge

[0078] The zeta potential of the nanoparticles was measured using an Ultrasizer (Marlven Panalytical) in multi-angle light scattering mode.

[0079] Oligonucleotide release

[0080] As described in Example 9, the amount and rate of oligonucleotide release from the nanoparticles was measured by gel electrophoresis.

[0081] PEG density characterization

[0082] The amount of PEG content on the nanoparticle surface was measured by UV assay as described in Example 21.

[0083] Example

[0084] Polymer synthesis

[0085] The bioresorbable polymers identified in Examples 1-5 were synthesized according to the methods described in "Analysis and characterization of resorbable DL-lactide trimethylene carbonate copolyesters," Journal of Material Science: Materials in Medicine 4 (1993), pp. 381-88.

[0086] Example 1: Characterization of L-PLA:TMC Copolymer

[0087] This example describes a copolymer L-PLA:TMC in a ratio of 75:25. Table 1 shows the characterization data of the composition in this example in the form of a purified sample. To obtain a purified sample, the copolymer L-PLA:TMC was dissolved in chloroform (CHCl) at 2-5 wt%. 3) and precipitated in 10x isopropyl alcohol (IPA) and then dried under vacuum. For this example, IV(HFIP)=1.349 dL / g and the glass transition temperature of the polymer was determined to be 32.95°C.

[0088] Example 2: Characterization of D,L-PLA:TMC-PEG5K copolymer

[0089] This example describes a copolymer D,L-PLA:TMC-PEG5K ratio of 86.4:8.7:4.9, and the characterization data of the composition is shown in Table 1. For this example, IV(HFIP)=1.3 dL / g, and the glass transition temperature of the polymer was determined to be 31.7°C.

[0090] Example 3: Characterization of D,L-PLA:TMC-PEG5K copolymer

[0091] This example describes a copolymer D,L-PLA:TMC-PEG5K ratio of 73.4:21.8:4.8, and the characterization data of the composition is shown in Table 1. For this example, IV(HFIP)=1.2 dL / g, and the glass transition temperature of the polymer was determined to be 20.4°C.

[0092] Example 4: Characterization of D,L-PLA:TMC-PEG5K copolymer

[0093] This example describes a copolymer D,L-PLA:TMC-PEG5K in a ratio of 82:8:10. Table 1 shows the characterization data for the composition. For this example, IV(HFIP) = 1.0 dL / g, and the glass transition temperature of the polymer was determined to be 26.2°C.

[0094] Example 5: Characterization of D,L-PLA:TMC-PEG10K copolymer

[0095] This example describes a copolymer D,L-PLA:TMC-PEG10K in a ratio of 86.5:8.5:5, and the characterization data for the composition is shown in Table 1. For this example, IV(HFIP)=1.4 dL / g, and the glass transition temperature of the polymer was determined to be 34.5°C.

[0096] Table 1

[0097]

[0098]

[0099] Example 6: Oligonucleotide Description

[0100] This example describes the oligonucleotides used in the nanoparticle encapsulation examples.

[0101] The oligonucleotide used in nanoparticle encapsulation, called “Oligo-1”, is a 20-mer oligonucleotide with five nucleotides 2’O-methylated at each end of the oligonucleotide.

[0102] The oligonucleotide used in nanoparticle encapsulation, called “Oligo-2,” is C*G*A*C*G*C*C*C*C*T*C*T*T*C*C*C*C*G*C*T*G, no methylation, asterisks indicate phosphorothioated bonds.

[0103] The oligonucleotide used in nanoparticle encapsulation, called “Oligo-3,” is mC*mG*mA*mC*mG*C*C*C*C*T*C*T*T*C*C*C*mC*mG*mC*T*mG, where “m” indicates methylation and asterisks indicate phosphorothioated bonds.

[0104] Example 7: Nanoparticles of Oligo-1 in L-PLA:TMC Copolymer with Low Levels of Lipid Salt DOTAP

[0105] This example demonstrates encapsulation of Oligo-1 in L-PLA:TMC copolymer nanoparticles in the presence of low levels of lipid salt DOTAP, specifically 19 wt.% lipid salt DOTAP and a 1:1 ratio of lipid salt DOTAP to Oligo-1, as described herein.

[0106] Nanoparticles were prepared by dissolving approximately 160 mg of L-PLA:TMC 75:25 ("LT-75") polymer (described in Example 1) and 50 mg of lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride, Avanti Polar Lipids Inc) in 6 mL of dichloromethane at room temperature. 0.5 mL of a 100 mg / mL Oligo-1 aqueous solution (in DNase / RNase-Free distilled water, Invitrogen) was pipetted into the polymer / DOTAP oil solution. The resulting mixture was sonicated in ice water for 1 minute using a Branson SXF150 sonicator equipped with a 1 / 4" conical probe. The sonication was performed using a continuous mode with an amplitude of 45%. The water-in-oil (W / O) emulsion was placed on an oscillator at a speed of 100 rpm / min overnight. The separated mixture was sonicated again on ice water for 1 minute to produce a good dispersion. Then about 15 mL of a 5% aqueous solution of polyvinyl alcohol (Aldrich, Mowiol 4-88) was added to the dispersion. The resulting mixture was sonicated for 2 minutes using the same sonicator and probe on an ice water bath. The sonication was performed using a continuous mode with an amplitude of 45% to produce a water-in-oil emulsion. Next, 230 mL of deionized water was added to the emulsion under magnetic stirring at 500 rpm. The emulsion was stirred at room temperature overnight to remove the dichloromethane. This formed hardened particles, which were centrifuged at 5000 rpm, 4°C for 30 minutes (Beckman-Coulter The particles were collected using an Avanti-J15R centrifuge. The nanoparticles were re-dispersed in a 0.2 wt% polyvinyl alcohol solution and centrifuged again to remove residual chemicals. The supernatant was discarded. The clean nanoparticles were dispersed in 10 mL of deionized water. Approximately 1 mL of the dispersed nanoparticles was set aside for size and zeta potential characterization. The remaining dispersion was freeze-dried. A scanning electron microscope (SEM) image of the freeze-dried nanoparticles taken at 20,000X is shown in Fig.13 The nanoparticles were determined to have a spherical shape and were singular.

[0107] Example 8: Size and charge characterization of the nanoparticles in Example 7

[0108] This example demonstrates the characterization of the size and zeta potential of the nanoparticles formed according to Example 7.

[0109] The nanoparticle dispersion described in Example 7 was diluted 5-10 times with deionized water before testing. The size of the nanoparticle dispersion was characterized and the zeta potential was characterized by dynamic light scattering using a Zetasizer Ultra (Malvern Panalytical, Malvern, UK). The results are summarized in Table 2. The results are also presented in Figure 6 middle, Figure 6 The relationship between nanoparticle diameter (also called size) and the level of lipid loaded into the nanoparticles is illustrated. Figure 8 The relationship between zeta potential and the level of lipid loaded in the nanoparticles is shown.

[0110] Example 9: Characterization of oligonucleotide loading of nanoparticles in Example 7

[0111] This example describes the characterization of the oligonucleotide loading of nanoparticles. The results are shown in Table 2 and Figure 7 .

[0112] The nanoparticles were weighed and dissolved in 1 mL of dimethyl sulfoxide (Sigma Aldrich). The nanoparticle / dimethyl sulfoxide (DMSO) solution was incubated in a water bath at 37°C for 2 hours to completely dissolve the nanoparticles. In order to decomplex the oligonucleotides from the lipid salts, 200 μL of DMSO / nanoparticle solution was added to 500 μL of 100 mg / mL heparin (Sigma Aldrich) and 100 mM octyl BD-galactoside (glactactoside) (Sigma Alrdich) solution, dissolved in nuclease-free deionized water (Invitrogen). The solution was vortexed at room temperature for 5 minutes, placed on a shaking table at room temperature for 30 minutes, and then vortexed for another 5 minutes before running on an electrophoresis gel for quantification. For electrophoresis, two oligonucleotide standards with concentrations of 2 ng / L and 1 ng / L were prepared in nuclease-free water (Invitrogen). The oligonucleotide standard solution included heparin and octyl BD-galactoside at the same concentrations as in the nanoparticle sample to explain any fluorescence attributed to the reagents. Load 10 μL of each sample or standard into a microcentrifuge tube. Add 2 μL of 6X DNA Orange loading dye (Invitrogen) to each sample and mix thoroughly. Add all 12 μL of each mixture to the wells of a 10-well 4-20% TBE gel (Invitrogen) in 1X TBE buffer. Run the gel at 250V for 25 minutes. Remove the gel and stain with 1X SybrGold (50,000X stock diluted in 1X TBE buffer (Invitrogen)) for 20 minutes with gentle shaking. Image the gel using Image Ready software (Biorad) on the BioRad Gel Doc system. Using the standards with Image Ready software (Biorad), create a standard curve and determine the concentration of the unknown samples based on the standard curve. The results are summarized in Tables 2 and Figure 7 In FIG, a representative run is shown, which illustrates the relationship between the loading amount (wt %) of nucleic acid and the level of lipid loaded in the nanoparticles.

[0113] Example 10: Nanoparticles of Oligo-1 in L-PLA:TMC Copolymer with Intermediate Levels of Lipid Salt DOTAP

[0114] This example demonstrates encapsulation of Oligo-1 in L-PLA:TMC copolymer nanoparticles in the presence of moderate levels of lipid salt DOTAP, specifically 26 wt.% lipid salt DOTAP and a 3:2 ratio of lipid salt DOTAP to Oligo-1, as described herein.

[0115] Nanoparticles are prepared by dissolving about 220 mg of L-PLA:TMC 75:25 polymer (as described in Example 1) and 100 mg of lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride, Avanti Polar Lipids Inc) in 8 mL of dichloromethane at room temperature. 0.5 mL of 130 mg / mL Oligo-1 aqueous solution (in DNase (deoxyribonuclease) / Rnase (ribonuclease)-free distilled water, Invitrogen) is pipetted into the polymer / DOTAP oil solution. Nanoparticles are prepared and cleaned according to the same procedure described in Example 7. Clean nanoparticles are dispersed in 10 mL of deionized water. About 1 mL of dispersed nanoparticles are set aside for size and zeta potential characterization. The remaining dispersion is lyophilized.

[0116] Nanoparticle size and zeta potential were measured as described in Example 8, and oligonucleotide loading was measured as described in Example 9. The results are summarized in Table 2. A representative run is shown in Figure 6-8 middle.

[0117] Example 11: Nanoparticles of Oligo-1 in L-PLA:TMC Copolymer with High Levels of Lipid Salt DOTAP

[0118] This example demonstrates encapsulation of Oligo-1 in L-PLA:TMC copolymer nanoparticles in the presence of high levels of lipid salt DOTAP, specifically 32 wt.% lipid salt DOTAP and a 2:1 ratio of lipid salt DOTAP to Oligo-1, as described herein.

[0119] Nanoparticles are prepared by dissolving about 160mg L-PLA:TMC 75:25 polymer (as described in Example 1) and 100mg lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride, Avanti Polar Lipids Inc) in 6mL dichloromethane at room temperature. 0.5mL of 100mg / mL Oligo-1 aqueous solution (in DNase / Rnase-free distilled water, Invitrogen) is pipetted into polymer / DOTAP oil solution. Nanoparticles are prepared and cleaned according to the same procedure described in Example 7. Clean nanoparticles are dispersed in 10mL deionized water. Set aside about 1mL of dispersed nanoparticles for size and zeta potential characterization. Remaining dispersion is lyophilized.

[0120] Nanoparticle size and zeta potential were measured as described in Example 8, and oligonucleotide loading was measured as described in Example 9. The results are summarized in Table 2. A representative run is shown in Figure 6-8 middle.

[0121] Example 12: Nanoparticles of Oligo-1 in L-PLA:TMC Copolymer with Low Levels of Lipid Salt DOTMA

[0122] This example demonstrates the encapsulation of Oligo-1 in L-PLA:TMC copolymer nanoparticles in the presence of low levels of the lipid salt DOTMA as described herein.

[0123] Nanoparticles are prepared by being dissolved in 6mL methylene chloride by about 160mg L-PLA:TMC 75:25 polymer (as described in Example 1) and 50mg lipid salt DOTMA (1,2-di-O-octadecene-3-trimethylammonium propane chloride, Avanti Polar Lipids Inc) at room temperature.0.5mL of 100mg / mL Oligo-1 aqueous solution (in DNase / Rnase-free distilled water, Invitrogen) is pipetted in polymer / DOTMA oil solution.Nanoparticles are prepared and cleaned according to the same procedure described in Example 7.Clean nanoparticles are dispersed in 10mL deionized water.Set aside about 1mL of dispersed nanoparticles for size and zeta potential characterization.Remaining dispersion is lyophilized.

[0124] Nanoparticle size and zeta potential were measured as described in Example 8, and oligonucleotide loading was measured as described in Example 9. The results are summarized in Table 2. A representative run is shown in Figure 6-8 middle.

[0125] Example 13: Nanoparticles of Oligo-1 in L-PLA:TMC Copolymer with High Levels of Lipid Salt DOTMA

[0126] This example demonstrates encapsulation of Oligo-1 in L-PLA:TMC copolymer nanoparticles in the presence of relatively high levels of the lipid salt DOTMA as described herein.

[0127] Nanoparticles are prepared by being dissolved in 6mL methylene chloride by about 160mg L-PLA:TMC 75:25 polymer (as described in Example 1) and 100mg lipid salt DOTMA (1,2-di-O-octadecene-3-trimethylammonium propane chloride, Avanti Polar Lipids Inc) at room temperature.1mL of 100mg / mL Oligo-1 aqueous solution (in DNase / Rnase-free distilled water, Invitrogen) is pipetted in polymer / DOTAP oil solution.Nanoparticles are prepared and cleaned according to the same procedure described in Example 7.Clean nanoparticles are dispersed in 10mL deionized water.Set aside about 1mL of dispersed nanoparticles for size and zeta potential characterization.Remaining dispersion is lyophilized.

[0128] Nanoparticle size and zeta potential were measured as described in Example 8, and oligonucleotide loading was measured as described in Example 9. The results are summarized in Table 2. A representative run is shown in Figure 6-8 middle.

[0129] Example 14: Nanoparticles of Oligo-1 in PLGA Copolymer with Low Levels of Lipid Salt DOTAP

[0130] This example demonstrates the encapsulation of Oligo-1 in PLGA copolymer nanoparticles in the presence of low levels of the lipid salt DOTAP as a comparison.

[0131] By mixing about 160 mg of PLGA polymer ( RG 756S, purchased from the poly (D, L-lactide-co-glycolide) of Evonik Industries, Germany) and 50mg lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride, Avanti Polar Lipids Inc) are dissolved in 6mL dichloromethane to prepare nanoparticles. 0.5mL of 100mg / mL Oligo-1 aqueous solution (in DNase / Rnase-free distilled water, Invitrogen) is pipetted into polymer / DOTAP oil solution. Nanoparticles are prepared and cleaned according to the same procedure described in Example 7. Clean nanoparticles are dispersed in 10mL deionized water. Set aside about 1mL of dispersed nanoparticles for size and zeta potential characterization. The remaining dispersion is lyophilized.

[0132] Nanoparticle size and zeta potential were measured as described in Example 8, and oligonucleotide loading was measured as described in Example 9. The results are summarized in Table 2.

[0133] Example 15: Nanoparticles of Oligo-1 in PLGA Copolymer with High Levels of Lipid Salt DOTAP

[0134] This example demonstrates the encapsulation of Oligo-1 in PLGA copolymer nanoparticles in the presence of higher levels of the lipid salt DOTAP as a comparison.

[0135] By mixing about 160 mg of PLGA polymer ( RG 756S, poly (D, L-lactide-co-glycolide) purchased from Evonik Industries, Germany) and 100mg lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride, Avanti Polar Lipids Inc) are dissolved in 6mL dichloromethane to prepare nanoparticles. 1mL of 100mg / mL Oligo-1 aqueous solution (in DNase / Rnase-free distilled water, Invitrogen) is pipetted into polymer / DOTAP oil solution. Nanoparticles are prepared and cleaned according to the same procedure described in Example 7. Clean nanoparticles are dispersed in 10mL deionized water. About 1mL of dispersed nanoparticles are set aside for size and zeta potential characterization. The remaining dispersion is lyophilized.

[0136] Nanoparticle size and zeta potential were measured as described in Example 8, and oligonucleotide loading was measured as described in Example 9. The results are summarized in Table 2. A representative run is shown in Figure 6-8 middle.

[0137] Table 2

[0138]

[0139]

[0140] Example 16: Oligonucleotide Release

[0141] The encapsulated oligonucleotides were released at pH 7 and pH 4. The results are summarized in Figure 9-10 , which shows the amount of nucleic acid released as a percentage of theoretical loading and a function of incubation time, as discussed herein.

[0142] In order to determine whether there is a burst release of encapsulated oligonucleotides at pH 7, 1 mL of 1 mg / mL oligonucleotide nanoparticle dispersion prepared according to Example 11 was incubated in a phosphate buffered saline (PBS) solution and supplemented with 10% fetal bovine serum and incubated at 37°C for 30 minutes, 1 hour, 4 hours or 24 hours. Samples for analysis were collected in two ways for comparison. In the first method, the incubated sample was taken out directly from the test tube and the electrophoresis gel (solid line) was run as described in Example 9. This method takes into account that the nanoparticles are too large to enter the gel, and the amount found in the gel is only the "free" oligonucleotide released in the assay. In the second method, the incubated sample was centrifuged at 10,000 rpm for 1 hour at 4°C (BeckmanCoulter) to separate the nanoparticles from the "free" oligonucleotides (dashed line). The supernatant of the centrifuged sample was then run on the electrophoresis gel. These two methods are used to determine whether the two methods artificially separate oligonucleotides from nanoparticles by force or by current.

[0143] To examine the release of encapsulated oligonucleotides at pH 4, 1 mL of 1 mg / mL oligonucleotide nanoparticle dispersion prepared according to Example 11 was incubated in phosphate citrate buffer at pH 4. The rest of the analysis (including incubation and gel electrophoresis) was the same as for the pH 7 samples.

[0144] Example 17: Nanoparticles of Oligo-1 in L-PLA:TMC and PLA-PEG Copolymers with Lipid Salt DOTAP

[0145] This example demonstrates the encapsulation of Oligo-1 oligonucleotide in 2K-5K copolymer nanoparticles of PLA-TMC and PLA-PEG in the presence of the lipid salt DOTAP.

[0146] Nanoparticles were prepared by dissolving approximately 120 mg of L-PLA:TMC 75:25 polymer (described in Example 1) and 40 mg of PLA-PEG copolymer (Sigma, methoxy poly(ethylene glycol)-b-poly(D,L-lactide), Mw=2K-5K) and 100 mg of lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride, Avanti Polar Lipids Inc) in 6 mL of dichloromethane at room temperature. 1 mL of 100 mg / mL Oligo-1 oligonucleotide aqueous solution (in DNase / RNase-free distilled water, Invitrogen) was pipetted into the polymer / DOTAP oil solution. The resulting mixture was sonicated in an ice bath for 1 minute using a Branson SXF150 sonicator equipped with a 1 / 4" conical probe. Sonication was performed using a continuous mode with C45% amplitude. The water-in-oil (W / O) emulsion was placed on a shaker at 100 rpm / min overnight. The separated mixture was sonicated again on ice water for 1 minute to produce a good dispersion.

[0147] Then add about 15mL 0.5wt / v% cholic acid (Sigma) aqueous solution to the dispersion.Use the same sonicator and probe to ultrasonicate the resulting mixture for 1 minute on an ice-water bath.Use continuous mode with 45% amplitude for ultrasonication to produce an oil-in-water emulsion.In addition, under magnetic stirring at 500rpm, 230mL deionized water is added to the emulsion.The emulsion is stirred overnight at room temperature to remove dichloromethane.This forms hardened particles, which are collected by centrifugation at 5000rpm, 4°C for 30 minutes (Beckman-Coulter centrifuge).The nanoparticles are redispersed in deionized water and centrifuged again to remove residual chemicals.Discard the supernatant.The clean nanoparticles are dispersed in 10mL deionized water.Set aside about 1mL of dispersed nanoparticles for size and zeta potential characterization.The remaining dispersion is freeze-dried.

[0148] Nanoparticle size and zeta potential were measured as described in Example 8, and oligonucleotide loading was measured as described in Example 9. The results are summarized in Table 4.

[0149] Example 18: Cleaning of particles using a tangential flow filtration system

[0150] This example demonstrates a cleaning process for cleaning nanoparticles without causing agglomeration of the particles.

[0151] From now on, tangential flow filtration technology is used to clean and concentrate the nanoparticle emulsion. The system uses a Pall Corporation (Port Washington, NY) Minimate EVO system, product ID: OAPMPUNV, with a membrane component MIDIKROS20CM 500K MPES 0.5MM FLL X FLL, Repligen Corporation (Waltham, MA), product ID: D02-E500-05-N, mPES membrane, 500kD, 20cm. First, the particle emulsion is concentrated from 400mL to 30mL. Then 70mL of deionized water is added to the concentrated emulsion under stirring. The emulsion is concentrated again to 30mL. This process is repeated twice. The emulsion is concentrated from 100mL to about 15mL for the third time. The cleaned particle emulsion is then pumped into a clean centrifuge tube.

[0152] Example 19: Nanoparticles of Oligo-2 in L-PLA:TMC with Lipid Salt DOTAP

[0153] This example demonstrates the encapsulation of Oligo-2 oligonucleotides in PLA-TMC copolymer nanoparticles in the presence of the lipid salt DOTAP.

[0154] Nanoparticles were prepared by dissolving approximately 160 mg of L-PLA:TMC 75:25 polymer (described in Example 1) and 100 mg of lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride, Avanti Polar Lipids Inc) in 6 mL of dichloromethane at room temperature. 1 mL of 100 mg / mL Oligo-2 oligonucleotide aqueous solution (in DNase / RNase-free distilled water, Invitrogen) was pipetted into the polymer / DOTAP oil solution. The Branson RT-PCR system equipped with a 1 / 4" tapered probe was used. The resulting mixture was sonicated in an ice bath for 1 minute using a SXF150 sonicator. The sonication was performed using a continuous mode with an amplitude of C45%. The water-in-oil (W / O) emulsion was placed on an oscillator at a speed of 100 rpm / min overnight. The separated mixture was sonicated again on ice water for 1 minute to produce a good dispersion. About 15 mL of a 0.5 wt / v% aqueous solution of bile acid (Sigma) was then added to the dispersion. The resulting mixture was sonicated using the same sonicator and probe on an ice water bath for 1 minute. The continuous mode with an amplitude of 45% was used. The mixture was ultrasonically treated to produce an oil-in-water emulsion. In addition, 230 mL of deionized water was added to the emulsion under magnetic stirring at 500 rpm. The emulsion was stirred overnight at room temperature to remove the dichloromethane. This resulted in hardened nanoparticles that were cleaned using the method described in Example 18. Approximately 1 mL of the dispersed nanoparticles were set aside for size and zeta potential characterization. In the presence of trehalose, the remaining dispersion was lyophilized in a 5 mM histidine buffer (pH 4.0) with a weight ratio of 1:10 between particles and trehalose (Sigma) in the particle dispersion.

[0155] The lyophilized particles were reconstituted in both deionized water and PBS. No aggregation was observed in the reconstituted dispersions in both deionized water and PBS. The particle distribution is shown in Fig.11 .

[0156] Nanoparticle size and zeta potential were measured as described in Example 8, and oligonucleotide loading was measured as described in Example 9. The results are summarized in Table 4.

[0157] Example 20: Nanoparticles of Oligo-3 in L-PLA:TMC with Lipid Salt DOTAP

[0158] This example demonstrates the encapsulation of Oligo-3 oligonucleotides in PLA-TMC copolymer nanoparticles in the presence of the lipid salt DOTAP.

[0159] Nanoparticles were prepared by dissolving approximately 160 mg of L-PLA:TMC 75:25 polymer (described in Example 1) and 100 mg of lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride, Avanti Polar Lipids Inc) in 6 mL of dichloromethane at room temperature. 1 mL of 100 mg / mL Oligo-3 oligonucleotide aqueous solution (in DNase / RNase-free distilled water, Invitrogen) was pipetted into the polymer / DOTAP oil solution. The Branson RT-PCR system equipped with a 1 / 4" tapered probe was used. The resulting mixture was sonicated in an ice bath for 1 minute using a SXF150 sonicator. Ultrasonication was performed using a continuous mode of C45% amplitude. The water-in-oil (W / O) emulsion was placed on an oscillator overnight at a speed of 100 rpm / min. The separated mixture was sonicated again on ice water for 1 minute to produce a good dispersion. Then about 15 mL of 0.5 wt / v% cholic acid (Sigma) aqueous solution was added to the dispersion. The resulting mixture was sonicated for 1 minute using the same sonicator and probe on an ice water bath. Ultrasonication was performed using a continuous mode of 45% amplitude to produce a water-in-oil emulsion. In addition, 230 mL of deionized water was added to the emulsion under magnetic stirring at 500 rpm. The emulsion was stirred at room temperature overnight to remove dichloromethane. This resulted in hardened nanoparticles cleaned using the tangential flow filtration system described in Example 18. Approximately 1 mL of dispersed nanoparticles were set aside for size and zeta potential characterization. The remaining dispersion was freeze-dried as described in Example 19.

[0160] Nanoparticle size and zeta potential were measured as described in Example 8, and oligonucleotide loading was measured as described in Example 9. The results are summarized in Table 4.

[0161] Example 21: Characterization of PEG surface density and coverage on PLA-TMC-PEG particles

[0162] This example describes the characterization of the PEG content on the surface of nanoparticles made from the polymers of Examples 2, 3 and 5.

[0163] PEGylated nanoparticles were prepared by dissolving 160 mg of L-PLA:TMC-PEG5K 86.4:8.7:4.9 polymer (as described in Example 2) in 6 ml of dichloromethane at room temperature. Approximately 15 mL of 0.5 wt / v% cholic acid (Sigma) aqueous solution was then added to the polymer dichloromethane solution. The resulting mixture was sonicated for 1 minute using the same sonicator and probe on an ice-water bath. Ultrasonication was performed using a continuous mode of 45% amplitude to produce an oil-in-water emulsion. In addition, 230 mL of deionized water was added to the emulsion under magnetic stirring at 500 rpm. The emulsion was stirred overnight at room temperature to remove dichloromethane. This resulted in hardened nanoparticles that were cleaned using the tangential flow filtration system described in Example 18.

[0164] In the same manner as above, PEGylated nanoparticles were prepared from L-PLA:TMC-PEG5K polymer 73.4:21.8:4.8 (as described in Example 3) and L-PLA:TMC-PEG10K polymer 86.5:8.5:5 (as described in Example 5). The PEG content on the nanoparticles was determined by UV detection using the complexation reaction of PEO with molybdophosphoric acid. The PEG concentration was determined based on the absorbance difference between the blank and the test solution using a calibration curve. According to Koopal et al. (Effect of the molecular weight of polyethylene oxide on the determination of its concentration in aqueous solution, Talanta, 1982, Vol. 29, pp. 495-501), this method has no PEO molecular weight dependence. Therefore, a calibration curve was established using a PEG with a molecular weight of 5K at different concentrations (10-500ug / mL). A blank was obtained from deionized water.

[0165] The tested PEG content of each batch of nanoparticles is listed in Table 3. The PEG content on the particles is close to its content in the polymer, which means that most of the PEG is located on the particle surface.

[0166] Table 3

[0167]

[0168] Example 22: Nanoparticles of Oligo-2 in L-PLA:TMC Copolymer with Lipid Salt DOTAP

[0169] This example demonstrates the encapsulation of a model Oligo-2 oligonucleotide in PLA-TMC-PEG terpolymer nanoparticles in the presence of the lipid salt DOTAP.

[0170] Nanoparticles were prepared by dissolving about 100 mg L-PLA:TMC:PEG 73.4:21.8:4.8 ternary polymer (as described in Example 3) and 100 mg lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride, Avanti Polar Lipids Inc) in 6 mL of dichloromethane at room temperature. 1 mL of 100 mg / mL Oligo-2 aqueous solution (in DNase / Rnase-free distilled water, Invitrogen) was pipetted into the polymer / DOTAP oil solution. Nanoparticles were prepared and cleaned according to the same procedure described in Example 18. About 1 mL of dispersed nanoparticles were set aside for size and zeta potential characterization. The remaining dispersion was freeze-dried in the presence of trehalose (Sigma) with a weight ratio of 1:5 between particles and trehalose. Freeze-dried particles were reconstructed in deionized water and PBS. No particle aggregation was observed in deionized water or PBS.

[0171] Nanoparticle size and zeta potential were measured as described in Example 8, and oligonucleotide loading was measured with slight modifications as described in Example 9. The particles were first dispersed in acetone and left to stand at room temperature for at least half an hour. DMSO was then added to dissolve the particles. The volume ratio of DMSO to acetone was 4:1. A transparent particle DMSO / acetone solution was obtained and gel electrophoresis was performed. The PEG density on the surface of the nanoparticles was measured as described in Example 21, and can be corrected according to the predicted Example 28. The results are summarized in Table 4.

[0172] Example 23: Nanoparticles of Oligo-3 in L-PLA:TMC-PEG Copolymer with Lipid Salt DOTAP

[0173] This example demonstrates the encapsulation of a model Oligo-3 oligonucleotide in PLA-TMC-PEG terpolymer nanoparticles in the presence of the lipid salt DOTAP.

[0174] Nanoparticles are prepared by dissolving about 100mg L-PLA:TMC:PEG 73.4:21.8:4.8 terpolymers (as described in Example 3) and 100mg lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride, Avanti Polar Lipids Inc) in 6mL dichloromethane at room temperature. 1mL of 100mg / mL Oligo-2 aqueous solution (in DNase / Rnase-free distilled water, Invitrogen) is pipetted in polymer / DOTAP oil solution. Nanoparticles are prepared and cleaned according to the same procedure described in Example 18. Set aside about 1mL of dispersed nanoparticles for size and zeta potential characterization. As described in Example 22, remaining dispersion is freeze-dried.

[0175] Nanoparticle size and zeta potential were measured as described in Example 8, and oligonucleotide loading was measured with slight modifications as described in Example 9. The particles were first dispersed in acetone and left to stand at room temperature for at least half an hour. DMSO was then added to dissolve the particles. The ratio of DMSO to acetone was 4:1. A transparent particle DMSO / acetone solution was obtained and gel electrophoresis was performed. The PEG density on the nanoparticle surface was measured as described in Example 21, and can be corrected according to the predicted Example 28. The results are summarized in Table 4.

[0176] Example 24: Nanoparticles of Oligo-3 in PEG:L-PLA:TMC Copolymer with Lipid Salt DOTMA

[0177] This example demonstrates the encapsulation of a model Oligo-3 oligonucleotide in PLA-TMC-PEG terpolymer nanoparticles in the presence of the lipid salt DOTAP.

[0178] Nanoparticles are prepared by being dissolved in 6mL methylene chloride by about 100mg L-PLA:TMC:PEG 73.4:21.8:4.8 terpolymer (as described in Example 3) and 100mg lipid salt DOTMA (1,2-di-octadecene-3-trimethylammonium propane chloride, Avanti PolarLipids Inc) at room temperature.1mL of 100mg / mL Oligo-2 aqueous solution (in DNase / Rnase-free distilled water, Invitrogen) is pipetted in polymer / DOTAP oil solution.Nanoparticles are prepared and cleaned according to the same procedure described in Example 18.Set aside about 1mL of dispersed nanoparticles for size and zeta potential characterization.As described in Example 22, remaining dispersion is freeze-dried.

[0179] Nanoparticle size and zeta potential were measured as described in Example 8, and oligonucleotide loading was measured with slight modifications as described in Example 9. The particles were first dispersed in acetone and left to stand at room temperature for at least half an hour. DMSO was then added to dissolve the particles. The volume ratio of DMSO to acetone was 4:1. A transparent particle DMSO / acetone solution was obtained and gel electrophoresis was performed. The PEG density on the surface of the nanoparticles was measured as described in Example 21, and can be corrected according to the predicted Example 28. The results are summarized in Table 4.

[0180] Example 25: Nanoparticles of Oligo-2 in PEG:L-PLA:TMC Copolymer with Lipid Salt DOTAP

[0181] This example demonstrates the encapsulation of Oligo-2 oligonucleotide in PEG-PLA–TMC terpolymer nanoparticles in the presence of the lipid salt DOTAP.

[0182] This example demonstrates the encapsulation of a model Oligo-2 oligonucleotide in PLA-TMC-PEG terpolymer nanoparticles in the presence of the lipid salt DOTAP.

[0183] Nanoparticles are prepared by dissolving about 100mg L-PLA:TMC:PEG 86.5:8.5:5 terpolymer (as described in Example 5) and 100mg lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride, Avanti Polar Lipids Inc) in 6mL dichloromethane at room temperature. 1mL of 100mg / mL Oligo-2 aqueous solution (in DNase / Rnase-free distilled water, Invitrogen) is pipetted into polymer / DOTAP oil solution. Nanoparticles are prepared and cleaned according to the same procedure described in Example 18. Set aside about 1mL of dispersed nanoparticles for size and zeta potential characterization. As described in Example 22, remaining dispersion is freeze-dried.

[0184] Nanoparticle size and zeta potential were measured as described in Example 8, and oligonucleotide loading was measured with slight modifications as described in Example 9. The particles were first dispersed in acetone and left to stand at room temperature for at least half an hour. DMSO was then added to dissolve the particles. The volume ratio of DMSO to acetone was 4:1. A transparent particle DMSO / acetone solution was obtained and gel electrophoresis was performed. The PEG density on the surface of the nanoparticles was measured as described in Example 21, and can be corrected according to the predicted Example 28. The results are summarized in Table 4.

[0185] Example 26: Nanoparticles of Oligo-2 in PEG:L-PLA:TMC and LT75 Copolymers with Lipid Salt DOTAP

[0186] This example demonstrates the encapsulation of Oligo-2 oligonucleotide in PEG-PLA–TMC and LT75 copolymer nanoparticles in the presence of the lipid salt DOTAP.

[0187] Nanoparticles are prepared by dissolving about 80 mg L-PLA:TMC:PEG (5K) 82:8:10 polymer (as described in Example 4) and 100 mg lipid salt DOTAP (1,2-dioleoyl-3-trimethylammonium-propane chloride, Avanti Polar Lipids Inc) in 6 mL of dichloromethane at room temperature. 1 mL of 100 mg / mL model Oligo-2 oligonucleotide aqueous solution (in DNase / Rnase-free distilled water, Invitrogen) is pipetted into the polymer / DOTAP oil solution. Nanoparticles are prepared and cleaned according to the same procedure described in Example 16. Clean nanoparticles are dispersed in 10 mL of deionized water. About 1 mL of dispersed nanoparticles are set aside for size and zeta potential characterization. The remaining dispersion is freeze-dried as described in Example 22.

[0188] Nanoparticle size and zeta potential were measured as described in Example 7, and oligonucleotide loading was measured with slight modifications as described in Example 9. The particles were first dispersed in acetone and allowed to stand at room temperature for at least half an hour. DMSO was then added to dissolve the particles. The ratio of DMSO to acetone was 4:1. A transparent particle DMSO / acetone solution was obtained and gel electrophoresis was performed. The PEG content on the surface of the nanoparticles was measured as described in Example 21. The high PEG content tested indicates complexation of the reagent with the oligonucleotide and / or lipid salt, and can be corrected according to the prophetic Example 28. The results are summarized in Table 4.

[0189] Table 4

[0190]

[0191]

[0192] *Low levels due to assay development variability, as described in Example 17

[0193] The measured PEG wt% values ​​obtained in Examples 22, 23, 24, 25 and 26 can be corrected according to Prophecy Example 28.

[0194] Example 27: Gel extraction assay

[0195] Fig.12 Gel assays for specific examples of standards, extracts, and nanoparticles are shown, as described in the Examples above.

[0196] Prophetic Example 28: Background Reading Determination of PEG Surface Density and Coverage

[0197] This example demonstrates a method to determine the background reading for the PEG surface density and coverage assays to allow the initial PEG reading to be adjusted for the background reading. Background readings can be caused by nonspecific binding in the assay, thus resulting in positive values ​​for PEG when PEG is not present. Performing this correction allows for more accurate corrected values ​​for PEG surface density and particle coverage produced by PLA-PEG or PLA-TMC-PEG. Background readings are based on particles made with LT-75, ASO, lipid salts, and no PEG.

[0198] For nanoparticles containing Oligo-2 and DOTAP, nanoparticles of LT-75, Oligo-2 and DOTAP were prepared (as described in Example 19) and analyzed by assay (as described in Example 21) for PEG surface density and coverage to determine background readings for PEG.

[0199] To estimate corrected values ​​for PEG surface density and coverage, values ​​obtained from background readings were subtracted from those for PEG containing nanoparticles.

[0200] The invention of the present application has been described above in general terms and in conjunction with specific embodiments. It will be apparent to those skilled in the art that various modifications and variations may be made to the embodiments described herein without departing from the spirit and scope of the present invention. Therefore, the embodiments are intended to cover such modifications and variations of the present invention as long as such modifications and variations are within the scope of the appended claims and their equivalents.

Claims

1. A preparation comprising a plurality of bioabsorbable particles, each bioabsorbable particle comprising: polymer matrix; antisense oligonucleotides (ASOs) encapsulated in a polymer matrix; and A cationic lipid encapsulated within a polymer matrix, wherein the plurality of bioresorbable particles comprises at least about 1% by weight antisense oligonucleotide (ASO).

2. The formulation of claim 1, wherein the average particle size of the plurality of bioresorbable particles is less than 300 nm.

3. The formulation of any one of claims 1-2, wherein the plurality of bioresorbable particles comprises at least about 5% by weight ASO.

4. The formulation of any one of claims 1-3, wherein the plurality of bioresorbable particles comprises at least about 10% by weight ASO.

5. The formulation of any one of claims 1-4, wherein the plurality of bioresorbable particles comprises at least about 15% by weight ASO.

6. The formulation of any one of claims 1-5, wherein the polymer matrix comprises trimethylene carbonate (TMC).

7. The formulation of any one of claims 1-6, wherein the polymer matrix comprises a copolymer of TMC and polylactic acid (PLA).

8. The formulation of claim 7, wherein the ratio of TMC to PLA is about 25:

75.

9. The formulation of any one of claims 1-8, wherein the polymer matrix comprises poly(lactic-co-glycolic acid) (PLGA) copolymer.

10. The formulation of any one of claims 1-9, further comprising a surface polymer attached to the surface of each bioresorbable particle.

11. The formulation of claim 10, wherein the surface polymer comprises polyethylene glycol (PEG).

12. The formulation of claim 11, wherein the bioresorbable particles comprise at least 5 wt% PEG.

13. The formulation of any one of claims 1-12, wherein the plurality of bioresorbable particles comprises from about 10% to about 40% by weight of the cationic lipid.

14. The formulation of any one of claims 1-13, wherein the plurality of bioresorbable particles comprises from about 20% to about 30% by weight of the cationic lipid.

15. The formulation of any one of claims 1-14, wherein the plurality of bioresorbable particles comprises nanoparticles.

16. The formulation of any one of claims 1-14, wherein the plurality of bioresorbable particles comprises micronized particles.

17. A method for treating a patient in need thereof, the method comprising the steps of: Delivering a formulation according to any one of claims 1-16 to a patient; and Sufficient time is allowed for the polymer matrix to degrade and release the nucleic acid within the patient.

18. A method for preparing a bioabsorbable particle preparation, the method comprising: (a) dissolving a structural polymer and a cationic lipid in a solvent; (b) adding a nucleic acid having a length of 2 to 75 nucleotides to the dissolved structural polymer and cationic lipid; (c) sonicating the mixture of the structural polymer, the cationic lipid and the nucleic acid in a first sonication treatment to produce a water-in-oil emulsion; (d) adding an aqueous solution to the water-in-oil emulsion; (e) sonicating the water-in-oil emulsion in a second sonication treatment to produce a water-in-oil-in-water emulsion; (f) adding water to the water-in-oil-in-water emulsion; (g) collecting a plurality of particles from the water-in-oil-in-water emulsion; and (h) washing the plurality of particles.

19. The method of claim 18, wherein the cationic lipid and the structural polymer are dissolved in a ratio of about 1:4 mass ratio to about 1:1 mass ratio.

20. The method of claim 18 or 19, wherein the nucleic acid is an antisense oligonucleotide (ASO) loaded into the plurality of particles at about 5% to about 20% by weight.

21. The method of any one of claims 18 to 20, wherein the first ultrasonic treatment and the second ultrasonic treatment are performed in an ice bath.

22. The method of any one of claims 18-21, wherein the aqueous solution is a polyvinyl alcohol solution.

23. The method of any one of claims 18-22, wherein the step of collecting the plurality of particles from the emulsion is performed by centrifugation.

24. The method of any one of claims 18-23, further comprising lyophilizing the oil solution in the presence of a sugar and a buffer.

25. The method of claim 24, wherein the sugar is trehalose.

26. The method of any one of claims 24-25, wherein the buffer is histidine.

27. A method for treating a patient in need thereof, the method comprising the steps of: (a) delivering to a patient a plurality of particles, each particle comprising: (i) a polymer matrix; (ii) a nucleic acid having a length of 2 to 75 nucleotides encapsulated in said polymer matrix; and (iii) a cationic lipid encapsulated within a polymer matrix, wherein the ratio of the cationic lipid to the polymer matrix in each particle is from 1:4 by weight to about 1:1 by weight; and (b) allowing sufficient time for the polymer matrix to biodegrade within the patient and release the nucleic acid.

28. The method of claim 27, wherein the nucleic acid is an antisense oligonucleotide (ASO) loaded in a plurality of particles at about 5 wt% to about 20 wt%, and the cationic lipid is one of 1,2-bis-O-octadecenyl-3-trimethylammonium propane chloride (DOTMA) or 1,2-dioleoyl-3-trimethylammonium propane chloride (DOTAP).

29. The method of claim 27 or 28, wherein the polymer matrix biodegrades in the colon of the patient.

30. The method of any one of claims 27-29, wherein each particle further comprises a surface polymer on the surface of each particle, the surface polymer comprising polyethylene glycol (PEG).

31. The method of claim 30, wherein each particle comprises at least 5% by weight PEG.

32. The method of any one of claims 27-31, wherein the plurality of particles comprises nanoparticles.

33. The method of any one of claims 27-32, wherein the patient suffers from inflammatory bowel disease, cardiovascular disease, hypertension, chronic heart failure, diabetes, Parkinson's disease, prostate cancer, or chronic kidney disease.

34. A preparation comprising a plurality of bioresorbable particles, each bioresorbable particle comprising: (a) polymer matrix; (b) nucleic acids encapsulated in the polymer matrix; (c) a cationic lipid encapsulated in the polymer matrix; and (d) a surface polymer attached to the surface of each bioresorbable particle, wherein the surface polymer comprises polyethylene glycol (PEG) and each bioresorbable particle comprises at least 5 wt% PEG.